Meningkatkan Karakter Kepemimpinan Siswa dengan Model Pembelajaran Problem Based Learning pada Materi Daud Sang Pemimpin Kelas V SD Yos Sudarso Cigugur - Andri Suryadi; Yoseph Kristianto; Agustina Susi Indratni (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
In the era of accelerated digitalization, various new problems have emerged among students, especially in the current post-pandemic era. Even though the development of technology and science is growing rapidly, it has given rise to various student character anomalies that are emerging now. The Covid-19 pandemic has had a negative impact on the Indonesian education sector. So there is a kind of alibi that during the pandemic, students did not receive enough character education during the period of social restrictions. Therefore, efforts are needed to improve students' leadership character in the education sector which is supported by increasing the variables of independence, discipline and responsibility. This effort is in line with the values ​​of the Pancasila Student Profile which affirms student competence in the dimensions of faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation, independence, critical reasoning and creativity. The researcher assumes that to improve the leadership character of Class V students at Yos Sudarso Cigugur Elementary School based on Minimum Completeness Criteria (KKM), the researcher applies the Problem Based Learning model as a strategy to support the process of actively developing student independence in two research cycles. Researchers conducted Classroom Action Research "Improving Student Leadership Character with a Problem Based Learning Model on Material from Daud the Class V Leader of Yos Sudarso Cigugur Elementary School" as an effort to overcome learning loss caused by the Covid-19 pandemic.